2004
DOI: 10.1021/jm030363k
|View full text |Cite
|
Sign up to set email alerts
|

Finding More Needles in the Haystack:  A Simple and Efficient Method for Improving High-Throughput Docking Results

Abstract: The technology underpinning high-throughput docking (HTD) has developed over the past few years to where it has become a vital tool in modern drug discovery. Although the performance of various docking algorithms is adequate, the ability to accurately and consistently rank compounds using a scoring function remains problematic. We show that by employing a simple machine learning method (naïve Bayes) it is possible to significantly overcome this deficiency. Compounds from the Available Chemical Directory (ACD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 19 publications
4
95
0
Order By: Relevance
“…Thus, the average enrichment values for ECFP_4B at 1% are 42.3 and 43.5 for BKD and data fusion, respectively, with the corresponding 5% values being 13.1 and 13.5, respectively, demonstrating the utility of the methods discussed here for virtual screening purposes. Circular substructures of various sorts have been widely used for applications such as structure and substructure searching [21][22][23], constitutional symmetry [24], structure elucidation [25] and, most recently, probabilistic modelling of bioactivity where a full training-set is available [26,27]. The work reported here demonstrates that this type of fragment is also very well suited to virtual screening using multiple reference structures.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, the average enrichment values for ECFP_4B at 1% are 42.3 and 43.5 for BKD and data fusion, respectively, with the corresponding 5% values being 13.1 and 13.5, respectively, demonstrating the utility of the methods discussed here for virtual screening purposes. Circular substructures of various sorts have been widely used for applications such as structure and substructure searching [21][22][23], constitutional symmetry [24], structure elucidation [25] and, most recently, probabilistic modelling of bioactivity where a full training-set is available [26,27]. The work reported here demonstrates that this type of fragment is also very well suited to virtual screening using multiple reference structures.…”
Section: Resultsmentioning
confidence: 94%
“…2D and 3D QSAR can also be used to track docking errors. This method has been used by Novartis where a QSAR model is built from docking scores rather than observed activities, and this model is applied to that set to provide additional score weights for each compound (Klon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[24,[27][28][29][30] In practice, the naive Bayes classifier has been demonstrated to outperform other sophisticated classifiers in text characterization and anti-spam filtering, and has recently started to be applied in drug discovery. [31][32][33] In this study, a traditional naive Bayes classification was carried out, in which each atom type contributed equally and objectively in determining the final class membership of a compound. The high ROC accuracy and enrichment performance indicated that highly correlated atom-type descriptors did not have a clear negative impact on the performance of the classifier.…”
Section: Naive Bayes Classifiermentioning
confidence: 99%